Ulli Beier in der Ausstellung Das Gesicht der Götter, die letzte Generation von Yoruba Priestern (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 1995)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Art; Painting; Africa; Exhibitions; Photographs; Yoruba (African people)–Religion; Art Exhibition; Cultural Centre; Yoruba Art; Yoruba Priest; Performing Arts Center